A novel research method for workshops and co-production of interventions: using a secret Facebook group - Audrey Buelo; Alison Kirk; Ruth Jepson (Pilot and Feasibility Studies, 2020)
Abstract Background Co-production of interventions is reliant on good communication and consensus between participants and researchers, but attending in-person meetings and workshops is hard for time-constrained groups such as new mums, who may be geographically dispersed without reliable transport. Discussions with a lay advisory group resulted in the decision to hold a workshop over a secret Facebook group. The aim of this study was to test the feasibility of a secret Facebook group for co-production activities. In the example presented, the population was women with previous gestational diabetes, the topic was physical inactivity, and the purpose was to develop an acceptable physical activity intervention. Methods The researchers created a secret Facebook group with content similar to an in-person workshop that sequentially progressed to develop a programme theory for an intervention. The researcher posted 1–2 times per day for 14 days, and members of the group were invited to comment and discuss the content. Feasibility and acceptability of the group were analysed using Facebook analytics and a post-workshop survey. Results Twenty-one participants took part. In total, 521 comments were provided in response to 18 posts of varying types (average = 28.9 comments per post). The total word count of participant comments was 21,142 words. The workshop was viewed positively, with 20 of 21 participants saying they liked the workshop “somewhat” or “a great deal”, and felt the group was a safe and open environment to share opinions. When asked if they would take part in something like this again, 15 of 21 said “Yes”. Participants mentioned the format was convenient; it allowed them to reflect on their experiences, and they liked helping research progress. Those who say “maybe” said it was difficult finding time and depended on what else was going on. Conclusion Using a secret Facebook group as a method of co-production or as a workshop in the research process is a feasible and acceptable method. Social media holds significant potential for co-production and involvement in research for populations who are geographically dispersed or time-constrained, with an uncommon condition or other circumstances where in-person meetings are either not appropriate or not possible.